Characterization of Composite Film of Gelatin and Squid Pen Chitosan Obtained by High Hydrostatic Pressure - Huang, Ya-Ling; Wang, Da-Ming (Polymers, 2023)
In the present study, gelatin-based films incorporating squid pen chitosan obtained by high hydrostatic pressure (HHP chitosan) at varying proportions were prepared and their properties were compared with films containing untreated chitosan. The resulting films were characterized by analyzing the physical, morphological, mechanical and barrier properties. The addition of different ratios of HHP chitosan to the gelatin-based film yielded significant improvements in mechanical and moisture barrier properties. The reason for this might be that HHP chitosan contributed to a regular and dense microstructure of the composite films due to forming a three-dimensional network structure in gelatin-based films with enhanced intermolecular interactions. The FTIR spectra showed no new chemical bond formed by incorporating HHP chitosan into gelatin-based film. The SEM micrographs showed that the gelatin-based film fabricated with three types of chitosan had a homogeneous surface morphology, indicating good compatibility of the materials. Compared to the gelatin-based films containing untreated chitosan, films containing HHP chitosan significantly delayed oxidative deterioration in oil during storage. Therefore, the chitosan obtained by HHP treatment could have a potential application in edible gelatin-based films as packaging materials.